2018
DOI: 10.37358/rc.18.7.6402
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Enamel Surface Treated with Fluoride After Bleaching and Etching Erosive Processes

Abstract: The anti-erosion effect of fluoride on the enamel surface was investigated by ATR-FTIR, SEM and EDX techniques. Four extracted teeth (two incisors and two premolars) were initially bleached with carabamide peroxide and etched with ortho-phosphoric acid then fluoride treatment was applied. Significant differences in enamel composition and morphology were observed providing the effect of fluoride application in remineralization of teeth. Infrared spectroscopy was employed to probe the changes in enamel structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The results of our study show that, within the sensitivity of the applied method, the etching procedure significantly affected the dental enamel, in comparison with the bleaching method that used different concentrations of carbamide peroxide [12,13]. The results of this study are in agreement with previous literature reports [14,15].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results of our study show that, within the sensitivity of the applied method, the etching procedure significantly affected the dental enamel, in comparison with the bleaching method that used different concentrations of carbamide peroxide [12,13]. The results of this study are in agreement with previous literature reports [14,15].…”
Section: Resultssupporting
confidence: 91%
“…These modifications are associated with the demineralization process which occurs by application of the etching agent on the enamel surface of teeth. By etching procedure the degree of demineralization is higher than that resulting from bleaching treatments of teeth, as our previously studies revealed [12,13]. Figure 4 presents the initial surface of one incisor in comparison with its surface after the etching treatment with ortho-phosphoric acid.…”
Section: Atr-ir Spectroscopymentioning
confidence: 77%
See 1 more Smart Citation
“…After silicification microcrystalline cellulose can improve binding capability and drug release as a material in tablet formula-Sahoo et al: Interactions between Ibuprofen ... tions by direct compression, wet granulation, dry granulation, and extrusion/spheronization processes. [13][14][15] The present work was undertaken to analyze the binding interactions between ibuprofen and silicified-microcrystalline cellulose. Chemical structure of ibuprofen, silicon dioxide and microcrystalline cellulose is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, for every two fluoride ions, tencalcium ions and six phosphate ions are required to form one unit cell of fluorapatite (Ca10(PO4)6F2). This means that, in case of topical application of fluoride, the availability of calcium and phosphate ions can be the limiting factor for net enamel remineralization to occur [1,6,7].…”
mentioning
confidence: 99%